Eficiência da capina mecânica automatizada no controle de plantas daninhas na soja em semeadura direta no sistema orgânico - Canavessi , Hiago (2022)
Efficiency of automated mechanical weeding in controlling weeds in soybean under direct seeding in the organic system. Advisor: Neumárcio Villanova da Costa. Co-advisor: Emerson Fey. One of the main bottlenecks for organic production is the control of weeds, usually carried out mechanically manually as well as mechanically automated in some countries. These automated equipment operate based on recognition and guidance systems, via cameras and even a GPS system. Weed control is carried out by means of sub-superficial cutting of the roots carried out by cultivators. However, the efficiency of control can be affected due to the presence of vegetation cover on the soil surface, impairing the cutting of weeds and possibly causing uprooting of soybean plants. Therefore, the objective was to evaluate the efficiency of the automated weeding machine model CHOPSTAR® (Einböck) with camera guidance (ROW-GUARD®) of different cultivator systems and the type of soil cover in the management of weeds in soybean under no-tillage organic. The experimental design was in randomized blocks in a split-plot scheme, with four replications. The plots were composed of three types of cover crops (rye, black oats + fodder radish and fallow area). The subplots corresponded to five treatments, consisting of: weeding system with a “Flat Andorinha Wing” cultivator (Weeding Machine 1), weeding system with a “Flat Andorinha Wing” cultivator complemented with manual weeding in the sowing line (Weeding Machine 1 + CM), weeding system with a “Horizontal Flat Disc” type cultivator (Weeding Machine 2), in addition to a manually weeded control and another without weed control. The period that obtained the lowest indices of dry mass and weed density in the rye cover crops and in the consortium. Among the main weed species found in both evaluation periods, C. benghalensis, D. insularis and B. pilosa stood out. Weed management was more efficient when working with the cultivation of rye as a cover crop and as a cutting system Capinadora 1 (“Asa de Andorinha Plana”) complemented with manual weeding.